2000
DOI: 10.1007/s002280000202
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to reporting adverse drug reactions in northern Sweden

Abstract: Our investigation shows that the physicians in northern Sweden have a fairly good knowledge about the existing rules for reporting ADRs in Sweden. However, the attitudes leave room for considerable under-reporting due to matters related mainly to the medical impact of the reaction and of reporting it, but also to the scientific "paradox" of reporting only on suspicion and of course due to lack of time in the health care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
79
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 0 publications
18
79
1
1
Order By: Relevance
“…The physicians in particular have proven their good knowledge about the existing rules for reporting ADRs in the country. [14] However, there is a hint of under-reporting to take place because of the matters which relate mainly to the medical impact of the reaction and of reporting it, but also the scientific 'myth' of reporting only based on suspicions and due to the lack of time in the healthcare setting.…”
Section: Introductionmentioning
confidence: 99%
“…The physicians in particular have proven their good knowledge about the existing rules for reporting ADRs in the country. [14] However, there is a hint of under-reporting to take place because of the matters which relate mainly to the medical impact of the reaction and of reporting it, but also the scientific 'myth' of reporting only based on suspicions and due to the lack of time in the healthcare setting.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Failure to report ADEs is influenced by many factors, such as lack of time, indifference, malpractice litigation concerns, lack of motivation, lack of economic incentive, complacency, lack of knowledge on ADE reporting requirements, and negative attitudes. 5,6,8,9 In addition, reluctance to send reports based on mere suspicion of ADEs, lack of confidence in recognizing adverse drug reactions, misconceptions about ADE reporting, and difficulty in accessing means of reporting (eg, forms) [10][11][12][13][14][15][16] also affect the reporting of ADEs. ADE reporting is also hampered by healthcare professionals' attitudes toward reporting 17 and possibly by personal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…(7, 20, 21, 38-40, 58, 63-65) The severity of the reaction was the main factor determining the ADR report or not. (65) Hasford et al (64) and Ekman et al (63) indicated that the severity of the reaction, unusual reactions and reactions caused by a new drug were the main reasons motivating HCP to report ADRs.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%